2008
DOI: 10.1159/000145457
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Virga GFR Equation in a Renal Transplant Population

Abstract: Background: Virga and colleagues derived a glomerular filtration rate (GFR) equation which demonstrated a superior performance over Cockcroft-Gault (C-G) and modified diet in renal disease-isotope dilution mass spectrometry (MDRD-IDMS) formulas in chronic kidney disease (CKD) patients. Aim: To validate the performance of the Virga equation on 103 renal transplant patients. Methods: We compared the performances of the MDRD-IDMS, C-G and Virga equations using inulin clearance as a reference test. Error, accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…In our study, this equation estimated the highest GFR levels among creatinine-based equations and the lowest CKD prevalence among all equations, particularly in individuals aged ≥65 years. Similar findings have been previously reported when comparing the Virga and MDRD-4 formulae in adult renal transplant recipients [27]. In our study, the Virga equation showed very poor agreement with all other equations.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, this equation estimated the highest GFR levels among creatinine-based equations and the lowest CKD prevalence among all equations, particularly in individuals aged ≥65 years. Similar findings have been previously reported when comparing the Virga and MDRD-4 formulae in adult renal transplant recipients [27]. In our study, the Virga equation showed very poor agreement with all other equations.…”
Section: Discussionsupporting
confidence: 84%
“…In this regard, the results are consistent with our previous work. 16,20 For example, the IDMS demonstrated significantly negative bias in those with minimal renal dysfunction and improved bias especially with those with moderate to severe renal dysfunction, consistent with the literature of all eGFR equation and estimated iGFR. 13,21 Similarly, accuracy of IDMS and precision were significantly lower in patients with minimal renal dysfunction while the CKD-EPI was better particularly in those with minimal renal dysfunction.…”
Section: Discussionsupporting
confidence: 80%
“…When more than one CR was done, the lowest value was used, to avoid CR results possibly associated with acute renal impairment. Estimated glomerular ltration rates (eGFR's) were calculated in the original Modi cation of Diet in Renal Disease Study Group (MDRD) equation that uses age, sex, CR, black/ white ethnicity [17]. We did not adjust for ethnicity because Saskatchewan has only a small black population and the unadjusted eGFR equation has been preliminarily validated in a North American Indian population [18].…”
Section: Methodsmentioning
confidence: 99%